The influence of principal's leadership, discipline, and teacher motivation on the performance of public elementary school teachers - Herni, Herni; Hidayat, Saleh; Fatmasari, Rhini (Journal of Research in Instructional, 2024)
How well teachers do their jobs in the classroom has a direct bearing on how well their pupils do in school. In order to determine whether pupils are ready to join the commercial and industrial sector, the efficacy of their teachers is essential. Improving the efficiency of educators has a bearing on the quality of the human capital developed via schools. In order to better understand how teacher motivation affects performance, how discipline affects performance, and how principal leadership affects performance, this research will examine all three of these factors. Furthermore, the research evaluates the impact of principal leadership, teacher motivation, and disciplinary measures on student outcomes. The participants in this quantitative study were 295 educators from Banyuasin I District's State Elementary School. We used a simple random selection strategy to identify 75 instructors for our sample. Data collection was conducted through the administration of questionnaires, which were subsequently subjected to analysis via multiple linear regression methodologies. The influence of principal leadership exhibited a partial positive correlation with teacher performance, while teacher discipline also demonstrated a partial positive correlation with teacher performance; conversely, teacher motivation revealed no discernible partial impact on teacher performance. Furthermore, it was determined that principal leadership, discipline, and motivation collectively exerted a significant influence on student achievement.